2007
DOI: 10.1017/s1740925x08000021
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells can contribute to axon–glial dissociation and fibrosis in peripheral nerve

Abstract: Expression of the human epidermal growth factor receptor (EGFR) in murine Schwann cells results in loss of axon-Schwann cell interactions and collagen deposition, modeling peripheral nerve response to injury and tumorigenesis. Mast cells infiltrate nerves in all three situations. We show that mast cells are present in normal mouse peripheral nerve beginning at 4 weeks of age, and that the number of mast-cells in EGFR(+) nerves increases abruptly at 5-6 weeks of age as axons and Schwann cells dissociate. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…A follow-up study using reciprocal bone-marrow transplantation between Nf1 +/-and Nf1 +/+ mice provide evidence that an Nf1 +/-c-Kit expressing hematopoietic cell contributes strongly to the plexiform neurofibroma phenotype, independent of Cre-mediated recombination ). In contrast, recent studies have reported the generation of plexiform neurofibromas in a wildtype Nf1 environment (Wu et al 2008) and that wildtype mast cells can contribute to tumor formation (Monk et al 2007). With the data presented in this paper, we can now reconcile these seemingly disparate results, clarifying the role of the Nf1 +/-microenvironment in peripheral nerve sheath tumorigenesis.…”
Section: The Contribution Of the Nf1 Heterozygous Environmentsupporting
confidence: 48%
See 2 more Smart Citations
“…A follow-up study using reciprocal bone-marrow transplantation between Nf1 +/-and Nf1 +/+ mice provide evidence that an Nf1 +/-c-Kit expressing hematopoietic cell contributes strongly to the plexiform neurofibroma phenotype, independent of Cre-mediated recombination ). In contrast, recent studies have reported the generation of plexiform neurofibromas in a wildtype Nf1 environment (Wu et al 2008) and that wildtype mast cells can contribute to tumor formation (Monk et al 2007). With the data presented in this paper, we can now reconcile these seemingly disparate results, clarifying the role of the Nf1 +/-microenvironment in peripheral nerve sheath tumorigenesis.…”
Section: The Contribution Of the Nf1 Heterozygous Environmentsupporting
confidence: 48%
“…Mast cells are unlikely contribute to the generation of Schwann cell pocket defects, as they are not present during this phase of peripheral nerve sheath tumor initiation. We cannot rule out the possibility that Nf1 +/+ or Nf1 +/-mast cells may contribute to loss of axon/glial interaction at P90; previous reports suggest this may indeed be the case (Monk et al 2007 Figure 3A). In contrast, the mutant P90 Nf1 -/-nerves consistently had elevated phospho-Erk and phospho-S6 levels ( Figure 3B).…”
Section: Nf1mentioning
confidence: 73%
See 1 more Smart Citation
“…This could lead to an increase in blood flow and presence of collagen synthesizing cells 4 . However, if these phenomena are excessive, or collagen fibers deposited in a random manner at the site of the lesion, local fibrosis could occur 17 .…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, mastocytes produce and release a variety of chemical mediators related to vascular proliferation and vasodilatation 3 . They also produce proteolytic enzymes responsible for the degradation of the basal membrane and extracellular matrix, which contribute to fibroblast activation and collagen deposition 4 . On the other hand, blood flow and angiogenesis help with tissue nutrition and create an adequate microenvironment for the repair process 5 .…”
mentioning
confidence: 99%